Anatomical and technical bases of digestive surgery - Medeiros, Aldo Cunha; Azevedo, Italo Medeiros (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Purpose: To discuss relevant issues concerned to surgical anatomy of digestive tract organs and their influence on surgical technique and operative tactics. Methods: The literature for this review was collected with PubMed and SciElo search using the combination of digestive tract, esophagus, stomach, small bowel, colon, surgical anatomy, operative technique, and the specific terms for anatomy. Results: This review has permited to stablish and emphasize the most relevant details of surgical anatomy of digestive tract associated to the facilities and technical difficulties encountered by surgeons when operating esophagus, stomach and intestines. Conclusion: Surgical anatomy of digestive tract is rich in essential details for surgery of the organs involved in this area, assisting surgeons about technical facilities and difficulties encountered in the operating room.